KEANEKARAGAMAN JENIS KANTONG SEMAR (NEPENTHES SPP.) DI TUTUPAN LAHAN SEMAK BELUKAR DAN HUTAN SEKUNDER DUSUN GEMURUH KECAMATAN SELAKAU TIMUR KABUPATEN SAMBAS - Amanda, M Sapaat; Astiani, Dwi; Muin, Abdurrani (Universitas Tanjungpura, 2019)
Tropical forests have a complex vegetation structure, which supports habitat for various types of plant species. But the opening of forest land cover can affect it. Picther plan (Nepenthes spp.) is one type of plant that is in the area of tropical rainforest. Nepenthes spp. are a unique type of flora in terms of color and shape which makes this plant very desirable to be used as an ornamental plant that has quite good economic value. The purpose of this study was to determine the species diversity ofÂ Nepenthes spp. from two land cover.Â This study uses a double plot with sub-plots with a basic field survey method of laying plots using purposive sampling. The results of the study found four types of Nepenthes spp. in shrub land cover and only one species in secondary forest. The species found is N. ampullaria Jack, N. gracilis Korth, N. mirabilis and N. rafflessiana. Each index of diversity is N. ampullaria Jack 0.1253, N. mirabilis (Lour) Druce 0.1004, N. gracilis Korth 0.0314, N.rafflesiana Jack 0.0105. Nepenthes spp. dispersion index on shrub land cover is group and in secondary forest is uniform. This area is more commonly found Nepenthes spp. and its dominance is higher in bush cover than in secondary forests.Keywords: Nepenthes spp., Secondary forests, Shrubs, Species diversity